2010
DOI: 10.5194/hess-14-1477-2010
|View full text |Cite
|
Sign up to set email alerts
|

Stream depletion rate with horizontal or slanted wells in confined aquifers near a stream

Abstract: Abstract. Pumping in a vertical well may produce a large drawdown cone near the well. In this paper, the solution is first developed for describing the groundwater flow associated with a point source in a confined aquifer near a stream. Based on the principle of superposition, analytical solutions for horizontal and slanted wells are then developed by integrating the point source solution along the well axis. The solutions can be simplified to quasi-steady solutions by neglecting the exponential terms to descr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Recently, Tsou et al . [] presented analytical solutions for flow into horizontal wells in a confined aquifer near a stream.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tsou et al . [] presented analytical solutions for flow into horizontal wells in a confined aquifer near a stream.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they indicated that their solution can reduce to that of Zhan and Zlotnik [81] for the aquifer of infinitely horizontal extent. Most of studies in fact introduce this assumption to describe the flux to the horizontal well [84,117,240]. The second assumption for specifying the boundary along the horizontal well screens is the constant-head condition.…”
Section: Analytical and Semi-analytical Methodsmentioning
confidence: 99%
“…Generally, the governing equation describing the transient groundwater flow after taking the Fourier transforms reduces to an initial value problem. Applications of these transforms can be found, for example, in Tsou et al [84] who used exponential Fourier, Fourier sine, and finite Fourier cosine transforms to solve a 3-D groundwater flow problem for a confined aquifer with a slanted well near a stream, in Huang et al [85] who applied exponential Fourier, Fourier sine, and Laplace transforms to obtain an analytical solution for describing the head distribution in an unconfined aquifer with a single pumping horizontal well parallel to a fully penetrating stream, and in other literatures [10,86] employing the finite Fourier sine or cosine or both finite Fourier sine and cosine transforms to solve a variety of groundwater flow problems.…”
Section: Fourier Transformmentioning
confidence: 96%
See 1 more Smart Citation
“…The SDR ranges from zero to a certain value, which could be equal to or less than unity (Zlotnik, 2004). Tsou et al (2010) developed an analytical solution of the SDR for a slanted well in confined aquifers adjacent to a stream treated as a constanthead boundary. They indicated that a horizontal well parallel to the stream induces the steady-state SDR of unity more quickly than a slanted well.…”
Section: C-s Huang Et Al: Approximate Analysis Of Three-dimensionamentioning
confidence: 99%